Metabolic and immunologic aspects of fetoplacental insufficiency. (24th August 2016) - Bekmukhambetov, Yerbol; Mamyrbayev, Arstan; Dzharkenov, Timur; Kravtsova, Natalia; Utesheva, Zhanar; Tusupkaliev, Akylbek; Ryzhkova, Svetlana; Darzhanova, Klara; Bekzhanova, Maral
Abstract : Problem: The chronic placental insufficiency is the most common cause of intrauterine hypoxia, retardation of fetal growth, and other threatening conditions. Immune disturbances may occur in the system "mother–placenta–fetus." Method of study: Biochemical blood indicators were studied on an automated biochemical analyzer. Pattern of lymphocyte subpopulations was detected by direct membrane immunofluorescence. Results: Study revealed imbalance of immune parameters, caused by placental insufficiency (increase natural killers (CD16 +, CD56 + ), B lymphocytes (CD19 + CD3 − ), T and B lymphocytes with HLA‐DR + antigen, and early activation of immune cells (by CD25 + ), as well as disorders in apoptotic mechanisms (by CD95 + )). Conclusion: Placental insufficiency leads to abnormalities of the immune system in pregnant, parturient women and maternity patients which were evaluated by localization of activation markers CD25 + CD95 + on the CD3 +, CD4 +, CD8 +, CD16 +, CD56 + lymphocytes. This is reflected in the change of lymphocyte functions in newborns.